THE DETERMINANTS OF CAPITAL STRUCTURE: EVIDENCE FROM FIRMS LISTED ON FTSE-350 SHARE INDEX - deng, wanying (2020)
The major objective of this paper is to explore the determinants affecting the capital structure of UK firms. Additionally, this paper also uses the financial crisis as a starting point to explore the changes in the capital structure of UK companies when the economy is weak.The regression results of the fixed effects model are consistent with the main capital structure theories and previous empirical research conclusions. Therefore, this study finds that asset tangibility is positively correlated with the traditional leverage ratios, while profitability is negatively correlated with the three leverage ratios. Although other capital structure determinants show mixed results on the three leverage ratios, they still conform to the theoretical predictions of capital structure theory. Moreover, when the dummy variable of crisis was added into the original regression model, the financial crisis had a significant positive effect on the leverage ratio. This indicates that the 2007/2008 financial crisis contributed to a significant increase in UK corporate leverage. In summary, the capital structure of UK companies does not follow any specific capital structure theory, but it does illustrate the importance of several corporate characteristics to capital structure.